Uji Banding Terjadinya Andropause antara Laki-Laki yang Lingkar Pinggangnya Besar dan Normal di Kecamatan Jebres Surakarta - Andreas Agung Kurniawan; Andri Iryawan; Bhisma Murti (Nexus Biomedika, 2014)
Background: Andropause in men can be caused by large waist circumference. The population of Asian countries, including Indonesia, tends to undergo an increase of waist circumference. This study is aimed to compare the occurrence of andropause between men with large and normal waist circumference. Methods: This study was a non-experimental analytic observational study with cross-sectional approach conducted in Jebres in September-October 2014. The subjects were 40 men selected using simple random sampling technique. The data obtained from physical measurements and questionnaire-led interviews were analyzed using multivariate logistic regression test to control confounding factors. Results: Twelve out of 15 men with large waist circumference (> 90 cm) experienced andropause and 16 out of 25 men with normal waist circumference (? 90 cm) did not experience andropause. On the other hand, 5 out of 10 men aged < 50 years experienced andropause and 23 out of 30 men aged ? 50 years did not experience andropause. Conclusion: Men with large waist circumference have risk experiencing andropause 3.06 times higher than men with normal waist circumference, although in this study the result is not significant (OR = 3.06; CI = 95% 0.59 to 15.95; p = 0.184 ). Keywords: Andropause, Waist Circumference